Mould/dampness exposure at home is associated with respiratory disorders in Italian children and adolescents: the SIDRIA-2 Study. Issue 9 (18th August 2005) - Simoni, M; Lombardi, E; Berti, G; Rusconi, F; La Grutta, S; Piffer, S; Petronio, M G; Galassi, C; Forastiere, F; Viegi, G
Abstract : Aims: To report on the relation between home mould and/or dampness exposure and respiratory disorders in a large sample of children and adolescents in Italy, accounting for age at time of exposure. Methods: 20 016 children (mean age 7 years) and 13 266 adolescents (mean age 13 years) completed questionnaires on indoor exposures and respiratory symptoms/diseases. Statistical analyses were adjusted for sex, age, questionnaire's compiler, area of residence, season of interview, parental educational status, family history of asthma, rhinitis, eczema, chronic obstructive pulmonary disease, presence of gas water heaters, passive smoking, pets, and active smoking (only for adolescents). Population attributable risk % (PAR) was also computed. Results: Asthma was more strongly related to only early than to only current exposure, both in children (OR 1.80, 95% CI 1.41 to 2.30) and adolescents (OR 1.89, 95% CI 1.38 to 2.59). The same result was found for rhino-conjunctivitis (OR 1.46, 95% CI 1.17 to 1.82), in children, and for wheeze among adolescents (OR 1.56, 95% CI 1.15 to 2.11). In children, wheeze (OR 1.98, 95% CI 1.47 to 2.66) and eczema (OR 1.44, 95% CI 1.09 to 1.91) were more strongly related to mould/dampness when exposed both early and currently; the same occurred in adolescents for rhino-conjunctivitis (1.78, 95% CI 1.30 to 2.45). Although persistent cough/phlegm was significantly related to mould/dampness exposure in children, regardless of exposure timing, no significant association between mould/dampness exposure and eczema or cough/phlegm was found among adolescents. PAR estimates were higher for only early than only current exposures. Avoiding early only exposure would abate wheeze by 6%, asthma or cough/phlegm by 7%, rhino-conjunctivitis in children by 4%, and in adolescents, asthma by 6%, and wheeze by 4%. Conclusions: Respiratory disorders such as wheeze and asthma can often be explained by exposure to home mould/dampness, especially early in life. The association seems more evident in children than in adolescents. These findings may suggest the need for environmental prevention strategies.